Bringing the Community to the Uni—Critical Reflections on Youth Recreation Partnerships in Toronto - Ali, Adam Ehsan; Darnell, Simon C.; Dinunzio, Danielle (Frontiers in Sports and Active Living, 2022)
The focus of this paper is an evaluation of a recreation project partnership between a co-curricular university department and various youth community programs in downtown Toronto, Canada. The goal of the Hart House Youth Community Recreation Project (YCRP) is to build a bridge between the university and its neighboring communities through recreation, arts, and dialogue-based programming that responds to the needs and interests of community partners and their youth members. Informed by the understanding that university/community partnerships are often paradoxical, the study assessed understandings of the program from the perspectives of the stakeholders involved. To do so, semi-structured interviews were conducted with the following two groups: organizers and leaders from the youth community programs, and staff members coordinating the project from the co-curricular university department. The results indicate that meaningful opportunities can be created within such partnerships through the provision of access to unique resources and recreation spaces; inclusion of partners in planning and program delivery; and through forging meaningful relationships between university staff and the program participants. However, significant challenges to creating and sustaining such opportunities also exist, including structural and social inequities that result in participants feeling othered in program settings; the instability and “delicacy” of trust within partnerships; and funding structure and resources. The findings shed light on, and make recommendations about, the potential benefits that youth organizations might gain from participating in university-community recreation partnerships, as well as the paradoxical nature of delivering and maintaining these partnerships.